Association of Depression, Antidepressants With Atrial Fibrillation Risk: A Systemic Review and Meta-Analysis - Fu, Yonghui; Feng, Shenghui; Xu, Yingxiang; Yang, Yuanjian; Chen, Haibo; He, Wenfeng; Zhu, Wengen; Yin, Kang; Xue, Zhengbiao; Wei, Bo (Frontiers in Cardiovascular Medicine, 2022)
Background: Depression is a possible influence factor for the increased risk of atrial fibrillation (AF). Although several investigations have assessed their association, the results are still controversial. Therefore, we conducted a meta-analysis to evaluate the association between depression or using antidepressants and AF. Methods: We systemically performed the literature retrieval from two electronic databases PubMed and EMBASE until March 2022 to extract relevant data. The hazard ratios (HRs) and odds ratios (OR) from included studies with 95% confidence intervals (CIs) were adjusted into the risk ratio (RR) and pooled by using the random-effects model. Results: Totally 9 studies about the associations between depression or antidepressants and AF risk were included in this meta-analysis. Among them, 5 studies specifically analyzed the impact of antidepressants on the risk of AF. The outcomes of our analysis indicated that depression or depressive symptoms could increase AF risk (RR=1.15, 95% CI, 1.03-1.27, P<0.01). In addition, the use of antidepressants can also increase AF risk (RR=1.16, 95% CI, 1.07-1.25, P<0.001). These results remained unchanged when we remove the source of heterogeneity or adjust the analysis model into the fixed-effects model. Conclusions: Based on existing investigations, both depression and the use of antidepressants are closely related to the increase of AF risk. Keywords: atrial fibrillation; depression; antidepressants; risk factor; meta-analysis